Use of Constructed Wetlands to Reduce Pollution of Surface Waters by Tea Factory Effluent in Nandi Hills Tea Estates in Kenya - Gituku, M. B.; Simiyu, G. M.; Davies, T. C. (Africa Environmental Review Journal, 2015)
The study aimed at investigating the efficiency of treating tea factory effluent using constructed wetlands in Nandi Hills Tea Estates, Kenya. Total Suspended Solids (TSS), Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) were determined in tea factory effluent. Dissolved nitrates and phosphates were analyzed in stream water samples using standard methods for sampling and analysis. Results showed that untreated tea factory effluent had high levels of COD (6732 to 14800 mg/L) and TSS (1078 to 3400 mg/L), and a moderate level of BOD (44 to 53 mg/L). These values reduced after treatment with more than 95% of TSS and COD and 80% of BOD removed by the constructed wetlands. Removal efficiencies for the heavy metals; Cd, Pb, Cu and Zn, were 7.1%, 80.0%, 95.1% and 100% respectively. The high concentration of nitrates (6.6 ± 2.1 mg/L) in a stream receiving factory effluent, compared to the receiving river (0.6 ± 0.7 mg/L) showed that some improvements were needed on the wetlands. The study recommends that sludge flushed out of the sedimentation basin should be directed to a sand bed for filtration and drying and the effluent passed on to the surface cells where more bio-degradation would take place. A mechanism to remove colour from the effluent should also be explored to reduce the turbidity of receiving waters.